Pengaruh Kompetensi, Komunikasi Internal dan Budaya Organisasi Terhadap Kinerja Pegawai Kantor Dinas Sosial Kabupaten Alor - Syaidina Muhammad Ali (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the Effect of Internal CoSocial Service Office Employees of Alor Regency, either partially or simultaneously. In this study, the population and sample were 38 employees of the Social Services Office of Alor Regency. This type of research is a quantitative type, with data collection techniques namely interviews, questionnaires and observation. And the sampling technique in this study is a saturated sample. The results of this study indicate that: (1). There is an influence of competence on the performance of employees of the Alor Regency Social Service Office. This is evidenced by the significance value of the t test, which is 0.000 or 0.0%, where this value is smaller than the alpha value, which is 0.5 or 5%. (2). There is an influence of internal communication on the performance of employees of the Alor Regency Social Service Office. This is proven by the significance value of the t test, which is 0.011 or 0.11%, where this value is smaller than the alpha value, which is 0.5 or 5%. (3). There is an influence of organizational culture on the performance of employees of the Social Service Office of Alor Regency. This is proven by the significance value of the t test, which is 0.001 or 0.01%, where this value is smaller than the alpha value, which is 0.5 or 5%. Simultaneously the competency, internal communication and organizational culture variables affect the performance of employees of the Alor Regency Social Service Office. This is evidenced by the significance value of the F test which is 0.000 or 0.00% where this value is smaller than the alpha value which is 0.5% or 5%. (5). The magnitude of the influence of competence, internal communication and organizational culture on the performance of employees of the Social Services Office of Alor Regency is 83.2%. This is proven by multiple correlation tests and the coefficient of determination.